The metamorphosis of supernova SN 2008D/XRF 080109: A link between supernovae and GRBs/hypernovae - Mazzali, P; Valenti, S; Della Valle, M; Chincarini, G; Sauer, D; Benetti, S; Pian, E; Piran, T; D'Elia, V; Elias-Rosa, N; Margutti, R; Pasotti, F; et al. (2008)
The only supernovae (SNe) to show gamma-ray bursts (GRBs) or early x-ray emission thus far are overenergetic, broad-lined type Ic SNe (hypernovae, HNe). Recently, SN 2008D has shown several unusual features: (i) weak x-ray flash (XRF), (ii) an early, narrow optical peak, (iii) disappearance of the broad lines typical of SN Ic HNe, and (iv) development of helium lines as in SNe Ib. Detailed analysis shows that SN 2008D was not a normal supernova: Its explosion energy (E ≈ 6 × 1051 erg) and ejected mass [∼7 times the mass of the Sun (MFish eye)] are intermediate between normal SNe Ibc and HNe. We conclude that SN 2008D was originally a ∼30 M Fish eye star. When it collapsed, a black hole formed and a weak, mildly relativistic jet was produced, which caused the XRF. SN 2008D is probably among the weakest explosions that produce relativistic jets. Inner engine activity appears to be present whenever massive stars collapse to black holes.